IMPLEMENTASI PROGRAM KETAHANAN PANGAN DALAM UPAYA PEMENUHAN LUMBUNG PANGAN DESA BERKELANJUTAN DI DESA JUMPUTREJO, KECAMATAN SUKODONO, KABUPATEN SIDOARJO - Civica Silmi; Isna Fitria Agustina (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the implementation of the food security program in Jumputrejo Village, Sukodono Sub-district, Sidoarjo District, using Grindle's Policy Implementation Model. The method used is a descriptive qualitative approach with data collection through semi-structured interviews and observation. Research informants included the village head, agribusiness groups and communities involved in the program. The results show that although various agribusiness sectors have been identified as the focus of the food security program, policy implementation suffers from imbalances in the allocation of attention, as well as limitations in adequate resources and infrastructure. The main challenges faced include inequality of program benefits, budget mismatches with field needs, and low active participation of farmer groups in decision-making. In addition, constraints in inter-agency coordination and the power of actors in decision-making also affect the effectiveness of the program. The conclusion of this study is that the success of the food security program in Jumputrejo Village requires improvements in program management, increased community participation, and more targeted resource allocation.